Functional Encapsulating Structure for Wireless and Immediate Monitoring of the Fluid Penetration - Lim, Daseul; Hong, Insic; Park, Sang Uk; Chae, Jeong Woo; Lee, Seunggon; Baac, Hyoung Won; Shin, Changhwan; Lee, Jungheon; Roh, Yeonwook; Im, Chaewan; Park, Yoonseok; Lee, Geumbee; et al. (Advanced Functional Materials, 2022)
With the fast-paced development of biomedical electronics, monitoring physiological processes have become ubiquitous throughout the field of implantable devices. Nevertheless, inherent challenges remain extant when long-term applications are concerned. For the stable and reliable function of these devices, hermetic and biocompatible encapsulation is of paramount importance; however, extrinsic defects and intrinsic swelling properties of the encapsulating layer present the key limitation to ideal barrier performance. Thus, the ability to monitor biofluid penetration and predict the device's functional lifespan is necessary for safe and stable operation within the body. This paper presents the functional encapsulation structure that quantitatively measures the diffusion of fluids into the encapsulation layer. The hydrolysis of Magnesium (Mg) electrodes underneath the encapsulating material shows the capability to wirelessly monitor the water penetration rate and the presence of defects, such as pinholes and cracks, in the encapsulating material. The experiments conducted throughout this paper analyze the Mg thickness and geometry of the antenna to optimize the device's susceptivity to water penetration when submerged in aqueous environments. The facile fabrication process and the compatibility with prevailing implantable electronics further substantiate the device's usability in diverse applications where chronic implants are necessary for monitoring disease or administering required treatments.
Keywords: Bio-fluid transmission rate measurement; Biofluids; Electronics system; Flexible bio-integrated electronic system; Integrated electronics; Magnesium sensor; Organic thin film encapsulation; Organic thin-films; Pinhole detection; Rate measurements; Scattering effects; Surface scattering effect; Thin film encapsulation; Transmission rates; bio-fluid transmission rate measurement; flexible bio-integrated electronic systems; magnesium sensors; organic thin film encapsulation; pinhole detection; surface scattering effect